2017
DOI: 10.1002/hup.2574
|View full text |Cite
|
Sign up to set email alerts
|

Long-term antipsychotic use and brain changes in schizophrenia - a systematic review and meta-analysis

Abstract: Antipsychotic medication may associate with brain structure changes. More long-term follow-up studies taking into account illness severity measures are needed to make definitive conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 82 publications
1
40
0
Order By: Relevance
“…45 These findings suggest that the effects of dysregulation within these brain systems are complicated by competing influences on activity and affective expression. 10,51 It is also possible that subject groups are qualitatively different, in that at least some of the first-episode subjects may represent individuals who will not go on to experience further episodes. While a lower glutamate signal must be interpreted with some caution, this finding is consistent with a relative decrease in network activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 These findings suggest that the effects of dysregulation within these brain systems are complicated by competing influences on activity and affective expression. 10,51 It is also possible that subject groups are qualitatively different, in that at least some of the first-episode subjects may represent individuals who will not go on to experience further episodes. While a lower glutamate signal must be interpreted with some caution, this finding is consistent with a relative decrease in network activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition while subjects were medication free when scanned, they were not necessarily medication naïve; although lithium has been observed to have neuroprotective rather than pathological properties, recent meta-analyses examining possible neurostructural effects of antipsychotic exposure have been mixed. 10,51 It is also possible that subject groups are qualitatively different, in that at least some of the first-episode subjects may represent individuals who will not go on to experience further episodes. However, the known natural history of bipolar I disorder and the relatively greater symptoms in the first episode patients militate against this concern.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous meta-analysis on long-term antipsychotic effects on brain structures, higher antipsychotic doses associated with decrease in parietal lobe volume and increase in basal ganglia volume (Huhtaniska et al, 2017a). A recent very large cross-sectional study pooling data from over 4000 schizophrenia patients found associations between medication dose and lower cortical thickness in multiple regions, which persisted after controlling for negative symptom severity (van Erp et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The current key treatment of psychosis, regardless of its aetiology or the underlying illness, is antipsychotic medication. Suggested harmful effects of high dose long-term antipsychotic treatment on brain structure volumes in psychoses are a debated issue with no consensus (Fusar-Poli et al, 2013;Huhtaniska et al, 2017a). Gray matter reductions have also been detected in populations at high risk for psychosis (Wood et al, 2008) and drug naïve first episode schizophrenia patients (Leung et al, 2011), which most likely reflects the pathological process leading to illness onset.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects attributable to chronic antipsychotic exposure are often cumulative over a period of years. A meta‐analysis found associations between long‐term antipsychotic use and brain volume changes. Antipsychotics may also impact on brain plasticity and cognitive functioning.…”
mentioning
confidence: 99%